TINJAUAN YURIDIS TERHADAP KONSTRUKSI HUKUM BADAN USAHA MILIK DESA (BUMDesa) DI KABUPATEN BANYUMAS - Rizky Priambodo (MIH Unsoed, 2019)
Village-Owned Enterprises (BUMDesa) in the legislation do not specifically explain the form of legal entity, type of company on BUMDesa, form of BUMDesa accountability with BUMDesa business units, and types of civil legal entities in BUMDesa business units. Research entitled